Hyperthermia-related clinical trials on cancer treatment within the ClinicalTrials.gov registry. (18th August 2015) - Cihoric, Nikola; Tsikkinis, Alexandros; van Rhoon, Gerard; Crezee, Hans; Aebersold, Daniel M.; Bodis, Stephan; Beck, Marcus; Nadobny, Jacek; Budach, Volker; Wust, Peter; Ghadjar, Pirus
Abstract: Purpose : Hyperthermia has been shown to improve the effectiveness of chemotherapy and radiotherapy in the treatment of cancer. This paper summarises all recent clinical trials registered in the ClinicalTrials.gov registry. Materials and methods : The records of 175, 538 clinical trials registered at ClinicalTrials.gov were downloaded on 29 September 2014 and a database was established. We searched this database for hyperthermia or equivalent words. Results : A total of 109 trials were identified in which hyperthermia was part of the treatment regimen. Of these, 49 trials (45%) had hyperthermic intraperitoneal chemotherapy after cytoreductive surgery (HIPEC) as the primary intervention, and 14 other trials (13%) were also testing some form of intraperitoneal hyperthermic chemoperfusion. Seven trials (6%) were testing perfusion attempts to other locations (thoracic/pleural n = 4, limb n = 2, hepatic n = 1). Sixteen trials (15%) were testing regional hyperthermia, 13 trials (12%) whole body hyperthermia, seven trials (6%) superficial hyperthermia and two trials (2%) interstitial hyperthermia. One remaining trial tested laser hyperthermia. Conclusions : In contrast to the general opinion, this analysis shows continuous interest and ongoing clinical research in the field of hyperthermia. Interestingly, the majority of trials focused on some form of intraperitoneal hyperthermic chemoperfusion. Despite the high number of active clinical studies, HIPEC is a topic with limited attention at the annual meetings of the European Society for Hyperthermic Oncology and the Society of Thermal Medicine. The registration of on-going clinical trials is of paramount importance for the achievement of a comprehensive overview of available clinical research activities involving hyperthermia.